STRUKTUR PENYAJIAN TARI JEPIN ROTAN DI PONTIANAK - Shara Safitri; Ismunandar Ismunandar; Christianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractJepin Rotan dance in the territory of the town of Pontianak was one of the Jepin dance that this day still exists. Forms generated by the property Jepin Rotan dance have its own philosophy that is described by Jepin Rotan dance. This research is a qualitative research with a choreographic approach. The method used in this writing is descriptive analysis method, namely the effort to explain in detail with a systematic, factual and accurate analysis of the facts of the object under study. The form of research used in this study is qualitative. The technique of collecting data was obtained in the form of interviews for data, and observation techniques for photos and videos. The technique used in checking the validity of the data in this study is the technique of triangulation method. The results showed that the presentment structure of Jepin Rotan dance have several aspects, namely motion, theme, floor design, makeup, fashion, property, musical accompaniment and the show place. In addition, the design of implementation  Jepin Rotan dance can be applied to cultural arts learning at second grade of Senior High School in accordance with the 2013 curriculum.   Keywords : Presentation Structure, Tari Jepin Rotan, Pontianak City